Hubungan Antara Beban Kerja Dengan Stres Kerja Pada Pegawai Di Balai Pemasyarakatan Kelas I Medan - Adelia Lestari; Arif Fachrian (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study aims to see the correlation between workload and work stress on the staff of the Class I Penitentiary in Medan. The population of this study were all employees of the Class I Correctional Center in Medan, amounting to 142 employees, and the sample in this study amounted to 43 employees at the Class I Correctional Center in Medan. The sampling technique used was Random Sampling. This research method uses quantitative methods. Collecting data using a workload scale and a work stress scale measured using a Likert scale. The data analysis technique uses the Product Moment Correlation technique. Where the results of the study show a significant value with a correlation of p = 0.000 0.05, meaning that there is a positive relationship between workload and work stress on the staff of the Class I Correctional Center in Medan, with a determinant coefficient (r2) of 0.328 or 26.3%. In other words, the hypothesis can be accepted. The workload variable is classified as high (empirical mean = 73.40 and hypothetical mean = 55 where the difference is more than SD = 11,729), and for the work stress variable is high with (empirical mean = 94.30 and hypothetical mean = 67 ,5 where the difference is more than SD=8.921).